DEVELOPING A QUALITY STANDARD FOR BATIK WITH NATURAL DYES: A PROPOSAL TO IMPROVE BATIK COMPETITIVENESS - Rizal Priambudi; Anas Miftah Fauzi; Muslich (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
This study aimed to develop quality standards for batik using natural dyes to enhance the competitiveness of the product. The method used was the FACTS approach, which included stakeholder analysis, standard comparison, and standard testing. Data were collected through interviews of 25 respondents consisting of government officials, producers, consumers, and experts. The stakeholder analysis involved defining batik with natural dyes, setting quality parameters, gathering testing methods, and technical analysis using the Zachman Framework. Subsequently, a comparison was made between the proposed standards and international standards such as OEKO-TEX® Standard 100 and the Ecological and Recycled Textile Standard (ERTS). Standard testing was then conducted by integrating inputs from stakeholders on the drafted standards. An analysis of willingness to pay was conducted to identify the level of customer readiness to pay more for certified environmentally friendly batik products. Survey results showed that out of 97 respondents, about 87% were willing to pay an additional 20-25% for batik using certified natural dyes. Keywords: Batik, natural dyes, quality standards, sustainability, Zachman Framework